2015
DOI: 10.1016/j.marenvres.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Community variability and ecological functioning: 40 years of change in the North Sea benthos

Abstract: Using established associations between species traits (life history, morphological and behavioural characteristics) and key ecological functions, we applied biological traits analysis (BTA) to investigate the consequences of 40 years of change in two North Sea benthic communities. Ecological functioning (trait composition) was found to be statistically indistinguishable across periods that differed significantly in taxonomic composition. A temporary alteration to functioning was, however, inferred at both samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…To our knowledge, this is the first study comparing long‐term trends and multi‐decadal dynamics in multiple dimensions of functional community change across trophic groups and areas. Previous trait‐based studies on long‐term functional community change have focused on single organism groups separately, either zoobenthos (Gogina, Darr, & Zettler, ; Neumann & Kröncke, ; Veríssimo et al, ; Weigel, Blenckner, & Bonsdorff, ) or fish (Baptista, Martinho, Nyjtrai, Pardal, & Dolbeth, ; Barcelo, Ciannelli, Olsen, Johannessen, & Knutsen, ; Dencker et al, ; Frelat et al, ), and particularly multi‐trait compositional changes on local scale (Clare, Robinson, & Frid, ; Frid & Caswell, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study comparing long‐term trends and multi‐decadal dynamics in multiple dimensions of functional community change across trophic groups and areas. Previous trait‐based studies on long‐term functional community change have focused on single organism groups separately, either zoobenthos (Gogina, Darr, & Zettler, ; Neumann & Kröncke, ; Veríssimo et al, ; Weigel, Blenckner, & Bonsdorff, ) or fish (Baptista, Martinho, Nyjtrai, Pardal, & Dolbeth, ; Barcelo, Ciannelli, Olsen, Johannessen, & Knutsen, ; Dencker et al, ; Frelat et al, ), and particularly multi‐trait compositional changes on local scale (Clare, Robinson, & Frid, ; Frid & Caswell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, our results also show that an assessment of dynamics, that is trait turnover and multi‐trait compositional changes, in addition to the functional indices, is of importance for understanding the potential rate of change and type of functional change (identity of traits) that has occurred. Changes in trait composition have proven valuable for informing on long‐term changes in potential functioning in previous single trophic group studies, for example in North Sea zoobenthic infauna (Clare et al, ) and epifauna communities (Neumann & Kröncke, ) or coastal fish assemblages (Barcelo et al, ). In this study, long‐term changes in feeding habit and size where generally observed, suggesting potential shifts in the benthic and pelagic energy pathway (SuppInfo A: Table S5), specifically during certain time periods (SuppInfo B: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, examining changes in taxonomic and trait diversity simultaneously may best describe community dynamics (Dencker et al, ; Monnet et al, ; Villéger, Miranda, Hernández, & Mouillot, ). For instance, changes in species composition may not lead to changes in trait diversity if loser species are replaced by species with similar traits (Clare, Robinson, & Frid, ; Villéger et al, ; White, Montgomery, Storchová, Hořák, & Lennon, ). Conversely, declines of a few rare species with unique trait values may have major impacts on trait diversity without notable changes in species composition (Mouillot, Bellwood, et al, ; Mouillot et al, ; Violle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional diversity is sometimes used as the sole explanatory variable for ecosystem functioning, which on the one hand has been shown to be a stronger predictor than species richness in many circumstances, but on the other omits information on the actual underlying functional structure (the functional identity), leaving it open which functions may or may not be present and to which degree they are expressed (Gagic et al ). There are surprisingly few studies available where the traditional taxonomic approach of changing faunal communities is assessed in combination with a functional framework on empirically collected data (van der Linden et al , Clare et al ). This is however an asset for understanding the potentially changing functionality within a system along environmental change.…”
mentioning
confidence: 99%